Income tax evasion estimation in Hungary - Pálma Filep-Mosberger; Ádám Reiff (Magyar Nemzeti Bank, 2022)
This paper studies labour market tax avoidance in the 2010s in Hungary, following major labour market tax reforms in the beginning of the decade. First we show that aggregate time series are broadly consistent with a "whitening" process, in which a higher fraction of incomes are declared. However, as aggregate developments are driven by several, often unobservable factors, we cannot conclude that the observed phenomena are indeed caused by a whitening process in the labor market. Therefore in the second part of the paper we use several micro datasets to shed light on the nature of the whitening process. By comparing the consumption pattern of entrepreneurs (who might have undeclared incomes) and state sector employees (who are unlikely to have undeclared income), we show that income underreporting of entrepreneurs did decline in the 2010s. On the other hand, we find that the number of illegal employees - e.g. of those who work without any work contract - only temporarily declined in the aftermath of the financial crisis and seems to follow a procyclical pattern.
Keywords: H26; J21; J31; 330; labour market tax avoidance; illegal employment; income underreporting